146PAnatomic versus non-anatomic resection for hepatocellular carcinoma: A meta-analysis of high-quality studies. (24th November 2019) - Zhang, B; Chen, M; Cao, J; Pan, L; Liang, Y; Cai, X
Abstract: Background: This meta-analysis collected studies with propensity score matching analysis (PSM) or Randomized Controlled Trial(RCT) and focused on comparing the short-term and oncological outcomes of patients with HCC who underwent anatomic liver resection (AR) versus non-anatomic liver resection (NAR), to provide relatively high-level evidence of AR in treating patients with HCC in comparison with NAR. Methods: A systematic literature search was performed using the PubMed, Embase, Cochrane Library and Web of Science to identify studies comparing AR with NAR by June 2019. The Newcastle-Ottawa Quality Assessment Scale (NOS) was used to evaluate the quality of the research included. The data were analyzed using Review Manager (Version 5.3). Dichotomous data were calculated by odds ratio (OR) and continuous data were calculated by weighed mean difference (WMD) with 95% confidence intervals (CI). Results: A total of 11 studies (PSM=10; RCT=1) enrolling 2905 patients (AR = 1452; NAR=1453) with HCC were included in the present meta-analysis. For oncological outcomes, no significant differences were observed in disease-free survival (1 year: OR = 0.75, 95% CI:0.55∼1.03, P = 0.07; 3 year: OR = 0.85, 95% CI: 0.70∼1.03, P = 0.09; 5 year: OR = 0.87, 95% CI: 0.70∼1.10, P = 0.24) and overall survival (1 year: OR = 1.04, 95% CI:0.78∼1.38, P = 0.79; 3 year: OR = 0.88, 95% CI: 0.63∼1.23, P = 0.47; 5 year: OR = 0.82, 95% CI: 0.58∼1.17, P = 0.27) between the two groups. In addition, the pooled analysis suggested that no differences were found between the AR groups and NAR group with respect to operative time (WMD=17.98min, 95% CI: -2.18∼38.14, P = 0.08), blood loss (WMD=93.82ml, 95% CI: -32.68∼220.33, P = 0.15) and postoperative morbidity (OR = 0.88, 95% CI:0.57∼1.35, P = 0.55). Conclusions: The present PSM and RCT data meta-analysis suggests that there does not appear to be a significant difference in survival between patients undergoing AR or NAR for HCC. Simultaneously, AR does not seem to bring more prognostic benefits in oncological outcomes including disease-free survival and overall survival. Considering unavoidable bias, more high-quality RCTs are badly needed to determine whether AR OR NAR can become standard practice for treating HCC patients. Legal entity responsible for the study: Xiujun Cai is responsible for the governance, coordination and running of the study. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.